The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2134/agronj2017.12.0683
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Agronomic Practices to Maximize Feed Barley Yield, Quality, and Standability in Alberta, Canada. I. Responses to Plant Density, a Plant Growth Regulator, and Foliar Fungicides

Abstract: Core Ideas Chlormequat chloride did not markedly reduce height or lodging, but yield increased by 2% across environments. Chlormequat chloride improved barley quality through increased test weight in moderate stands (240 plants m−2). Foliar fungicides increased grain yield by 3% across environments, which overall had low disease pressure. Dual fungicide applications increased yield more than single applications only at the higher density (355 plants m−2). Greatest grain yield was achieved by 355 plants m−2, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
3
10
1
1
Order By: Relevance
“…Others have also reported a greater normalized difference vegetation index (NDVI), an indicator of photosynthetic leaf area, in barley treated with foliar fungicides(Perrott et al, 2018). FR, fungal resistant barley sprayed with the fungicide Twinline ® (BASF, Missisauga, ON) applied at the flag leaf emergence to boot stage at the rates outlined in the materials and methods; UN, fungal susceptible barley with no fungicide treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have also reported a greater normalized difference vegetation index (NDVI), an indicator of photosynthetic leaf area, in barley treated with foliar fungicides(Perrott et al, 2018). FR, fungal resistant barley sprayed with the fungicide Twinline ® (BASF, Missisauga, ON) applied at the flag leaf emergence to boot stage at the rates outlined in the materials and methods; UN, fungal susceptible barley with no fungicide treatment.…”
mentioning
confidence: 99%
“…Foliar fungal infections reduce photosynthetic area of leaves and decrease the filling of grain kernels(Poole & Arnaudin, 2014). Others have also reported a greater normalized difference vegetation index (NDVI), an indicator of photosynthetic leaf area, in barley treated with foliar fungicides(Perrott et al, 2018). Studies have also shown that fungi utilize plant simple sugars and likely hydrolyse starch to meet their energy requirements(Singh, Asthir, Bains, & Mann, 2009).…”
mentioning
confidence: 99%
“…Seeding rates were therefore incorporated into the current study to try to create a scenario with increased probability of lodging. Additionally, recent research has found interactions between seeding rate and PGR application (Perrott et al 2018). The effect of chlormequat chloride on spike length, test weight, and acid detergent fibre in feed barley in Alberta was different between target plant densities of 240 and 355 plants m −2 (Perrott et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Overall impacts of lodging depend on how early a plant lodges (Jedel and Helm 1991), weather events following lodging, and disease inoculum levels. Lodging risks can be cultivar specific (Clark and Fedak 1977) but are also affected by agronomic decisions such as seeding date or rate (O'Donovan et al 2012), seeding depth (Pinthus 1974), fertilization strategies (O'Donovan et al 2011), and potentially disease management (Turkington et al 2015;Perrott et al 2018) that affect plant height, plant health, and, likely as a result, stem strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation